Implementation of reduce, reuse, recycle (3R) movement to improve the students’ environmental literacy - Anisa, Nur; Ainayah, Ainun; Nafissah, Nur Azkiah; Riyanto, Sugeng; Endarsti, Dewi (Universitas Ahmad Dahlan, 2023)
Using strategy in protecting environment is very important, since it can encourage a caring attitude towards the surrounding environment. This research aims to find out the efforts of SD Muhammadiyah Karangkajen, a private elementary school in Yogyakarta, Indonesia, in implementing the policy of reuse, reduce, and recycle (3R) to improve environmental literacy for students. It is a qualitative research which collected the data through observation, documentation, and interviews. The results suggest that the efforts made to foster environmental literacy in students at SD Muhammadiyah Karangkajen through the 3R movement were carried out with supporting things such as refraction through culture, rules, the introduction of Adiwiyata program, and classroom learning based on the living environment.